Quantification of viral infection dynamics in animal experiments - Iwami, Shingo; Koizumi, Yoshiki; Ikeda, Hiroki; Kakizoe, Yusuke (Frontiers in Microbiology, 2013)
Analyzing the time-course of several viral infections using mathematical models based on experimental data can provide important quantitative insights regarding infection dynamics. Over the past decade, the importance and significance of mathematical modeling has been gaining recognition among virologists. In the near future, many animal models of human-specific infections and experimental data from high-throughput techniques will become available. This will provide us with the opportunity to develop new quantitative approaches, combining experimental and mathematical analyses. In this paper, we review the various quantitative analyses of viral infections and discuss their possible applications.